Sacral Fractures with Spondylopelvic Dissociation. Issue 5 (May 2018) - DeRogatis, Michael J.; Breceda, Adam P.; Lee, Patrick; Issack, Paul S.
Abstract : U-type or H-type sacral fractures are a result of very high energy injuries that separate the lumbar spine and upper sacrum from the lower sacrum and pelvis. Advances in acute trauma care have resulted in an increase in the number of patients who survive this injury. The choice of approach is dictated by several factors, including dorsal soft-tissue trauma, the need for neurological decompression, and the adequacy of sacral sagittal balance. Complication rates following surgical treatment are high and primarily are related to the soft tissues. This fracture pattern has a high association with polytrauma, major neurological injury (including cauda equina syndrome), and soft-tissue degloving injuries. While nonoperative management may be appropriate for patients who are expected to be bedbound or non-weight-bearing for at least 3 months, the majority of these injuries are treated surgically with iliosacral screws and spinal constructs that anchor the pelvis to the lower lumbar spine. Careful attention to damage-control principles, efficient surgical stabilization of the spondylopelvic injury and associated fractures, and early mobilization can lead to good functional outcomes following this potentially devastating injury.